Wideband performance limitations of the C-FDTD in the discretization impoverishment of a curved surface. Issue 5 (30th June 2020) - Fortes, Lucas Lobo Latorre; Gonçalves, Sandro Trindade Mordente
Abstract : Purpose: This paper aims to explore the limitations of the conformal finite difference time-domain method (C-FDTD or Dey–Mittra) when modeling perfect electric conducting (PEC) and lossless dielectric curved surfaces in coarse meshes. The C-FDTD is a widely known approach to reduce error of curved surfaces in the FDTD method. However, its performance limitations are not broadly described in the literature, which are explored as a novelty in this paper. Design/methodology/approach: This paper explores the C-FDTD method applied on field scattering simulations of two curved surfaces, a dielectric and a PEC sphere, through the frequency range from 0.8 to 10 GHz. For each sphere, the mesh was progressively impoverished to evaluate the accuracy drop and performance limitations of the C-FDTD with the mesh impoverishment, along with the wideband frequency range described. Findings: This paper shows and quantifies the C-FDTD method's accuracy drops as the mesh is impoverished, reducing C-FDTD's performance. It is also shown how the performance drops differently according to the frequency of interest. Practical implications: With this study, coarse meshes, with smaller execution time and reduced memory usage, can be further explored reliably accounting the desired accuracy, enabling a better trade-off between accuracy and computational effort. Originality/value: This paper quantifies the limitations of the C-FDTD in coarse meshes in a wideband manner, which brings a broader and newer insight upon C-FDTD's limitations in coarse meshes or relatively small objects in electromagnetic simulation.